ANTICANCER ACTIVITY OF GARCINIA MORELLA CHLOROFORM FRACTION AND ITS ACTIVE COMPOUND GARCINOL ON NEUROBLASTOMA - Choudhury, Bhaswati; Kandimalla, Raghuram; Bharali, Rupjyoti; Kotoky, Jibon (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of the present study is to evaluate the anticancer activity of G. morella fruit chloroform fraction and its isolated bioactive molecule garcinol on neuroblastoma cell line (SH-SY5Y). Method: Methanol extraction was performed for the G. morella fruits through cold maceration and further fractionated with chloroform. The presence of Garcinol was confirmed by measuring the melting point. Further, the bioactive chloroform fraction and pure Garcinol was tested for anticancer activity against SH-SY5Y cells through MTT assay. Result: The present study reveals the anticancer ability of bioactive chloroform fraction of G. morella fruit and its active molecule garcinol. Conclusion: G. morella fruit and its bioactive compound Garcinol have significant activity against neuroblastoma. This study opens an avenue to further elucidate the mechanism of action and development of alternative treatment of this dreaded disease. Â 